Gender differences in outcomes after aortic aneurysm surgery should foster further research to improve screening and prevention programmes. (29th August 2020) - Nicolini, Francesco; Vezzani, Antonella; Corradi, Francesco; Gherli, Riccardo; Benassi, Filippo; Manca, Tullio; Gherli, Tiziano
Abstract: Background: Gender-related biases in outcomes after thoracic aortic surgery are an important factor to consider in the prevention of potential complications related to aortic diseases and in the analysis of surgical results. Methods: The aim of this study is to provide an up-to-date review of gender-related differences in the epidemiology, specific risk factors, outcome, and screening and prevention programmes in aortic aneurysms. Results: Female patients affected by aortic disease still have worse outcomes and higher early and late mortality than men. It is difficult to plan new specific strategies to improve outcomes in women undergoing major aortic surgery, given that the true explanations for their poorer outcomes are as yet not clearly identified. Some authors recommend further investigation of hormonal or molecular explanations for the sex differences in aortic disease. Others stress the need for quality improvement projects to quantify the preoperative risk in high-risk populations using non-invasive tests such as cardiopulmonary exercise testing. Conclusions: The treatment of patients classified as high risk could thus be optimised before surgery becomes necessary by means of numerous strategies, such as the administration of high-dose statin therapy, antiplatelet treatment, optimal control of hypertension, lifestyle improvement with smoking cessation, weight loss and careful control of diabetes. Future efforts are needed to understand better the gender differences in the diagnosis, management and outcome of aortic aneurysm disease, and for appropriate and modern management of female patients.